Multilingualism in Hong Kong’s Formal and Informal Settings: A Brief Historical Review of The Development from The Early 1900s To the Late 2010s (JOURNAL OF ADVANCES IN LINGUISTICS, 2020)
This article aims at tracing back the making of multilingualism in Hong Kong from a socio-historical viewpoint. It primarily illustrates the linguistic profiles of Cantonese, English, and Putonghua in official domains throughout the colonial period and after the 1997 handover, secondarily describing their roles in Hongkongers’ daily life. The situation of other minor languages is mentioned in passing. The snapshots reveal that a) Cantonese has developed to be a powerless lingua franca of Hongkongers, b) English has become a powerful second language with high economic value that hugely outweighs Cantonese, and that c) Putonghua has been similar to a foreign language despite its official status on the mainland. Other heritage languages of ethnic minorities have existed since the early colonial period, but they have never entered the mainstream or vastly impacted the three dominating languages. The discussion concludes that Hong Kong has yet to be a typical multilingual metropolis where citizens are fluent or native in multiple languages. It is still fluctuating in between monolingualism and multilingualism, however, showing an inclination to the latter.